Swing Otto swing! - Milgrim, David (New York : Atheneum Books for Young Readers, 2004)
When Otto the robot has trouble learning to swing on vines like his monkey friends, he decides to make his own swing set instead.
"Pre-level 1, Recognizing Words'--Cover p. [4].
Keywords: Robots -- Fiction; Monkeys -- Fiction; Swings -- Fiction; Monkeys -- Juvenile fiction; Swings -- Juvenile fiction; Robots -- Juvenile fiction